Bioenergetics of the hockey match of Russia and the USA at the Olympic Games in Pyeongchang - Sivakov, V. I.; Cherkasov, I. F.; Matveeva, P. A.; Gladkih, E. S. (International Journal of Applied Exercise Physiology, 2020)
Objective: to substantiate the bioenergy of a hockey match for the game result of the hockey team of Russia and the USA at the Olympic Games in Pyeongchang.